Simulation modeling study on short circuit ability of distribution transformer. Issue 1 (February 2020) - Shiling, Zhang; Lin, Gong
Abstract: Under short circuit condition, the oil immersed distribution transformer will endure combined electro-thermal stress, eventually lead to the mechanical damage of the inner winding of distribution transformer, therefore it is necessary to study the short circuit ability of the oil immersed distribution transformer. In this paper, the typical current waveform of the distribution transformer under the short-circuit condition is analyzed theoretically. The short circuit fault simulation model of distribution transformer is built on the MATLAB/Simulink simulation platform, the short circuit waveform of the single phase, double phase and three phase short circuit is obtained. Further on the ANSYS simulation platform, three dimensional solid modeling of the three-phase five column transformer is carried out, the harmonic and transient field are applied to analyze the magnetic field distribution of the key components in distribution transformer under the short circuit condition, the internal cause of large short-circuit force in the winding of the distribution transformer under the short circuit condition is analyzed to certain extent. The results of the modeling and simulation show that the three phase short circuit current is larger than the single-phase and bi-phase short circuit current. Its value is 1.45 times the normal running current, which is the gradual damping asymmetrical short-circuit current. Magnetic induction intensity is in-homogeneous in the circumferential direction of the core column, and the degree of in-homogeneity varies along height. The magnetic density distribution under the short circuit condition is more than 6 times as much as the the normal condition. From the point of view of simulation modeling, short circuit ability of the oil immersed distribution transformer is analyzed, distribution characteristics of short circuit current and magnetic field of oil immersed distribution transformer under short circuit condition have been obtained, the theoretical reference value of the state characteristics and protection measures of oil immersed distribution transformer under the overload condition can be provided.